Efficacy of lanreotide 120 mg primary therapy on tumour shrinkage and ophthalmologic symptoms in acromegaly after 1 month. (5th May 2022) - Benderradji, Hamza; Vernotte, Elise; Soto Ares, Gustave; Woillez, Jean Philippe; Jannin, Arnaud; Perbet, Romain; Karnoub, Mélodie‐Anne; Soudan, Benoît; Assaker, Richard; Buée, Luc; Prevot, Vincent; Maurage, Claude‐Alain; et al.
Abstract: Introduction: Few studies have attempted to evaluate the early efficacy of first‐generation somatostatin analogues in somatotroph macroadenomas. Objective: To investigate the short‐term efficacy of primary therapy with lanreotide 120 mg at 1 and 3 months on tumour shrinkage and ophthalmologic symptoms in newly diagnosed patients with acromegaly. Design and Patients: This single‐centre retrospective study included 21 patients with de novo acromegaly resulting from pituitary macroadenoma, with optic chiasm compression (Grade ≤ 2) and/or cavernous sinus invasion, treated with a monthly injection of lanreotide 120 mg. Clinical, hormonal, ophthalmologic and magnetic resonance imaging scan evaluations were conducted after the first and the third months of treatment. Results: Tumour volume reduction was more pronounced at 1 month; mean volume change: −31.4 ± 19.5%, p  < .0001 than between the first and third month of treatment; mean volume reduction: −20.6 ± 13.4%, p  = .0009. The mean volume change between baseline and the third month was − 46.4 ± 21.6, ( p  < .0001). A significant volume reduction (≥25%) was observed in 61.9% of individuals (13/21) at the first month. Among 14 individuals with optic chiasm compression and visual field defects, visual field normalization or improvement were observed in seven cases (50%), stabilization in four cases (28.5%), and mild worsening in three cases (21.4%) at 1 month. The decrease in growth hormone and IGF‐1 serum values was significant at 1 month. Conclusions: Primary treatment with lanreotide 120 mg in patients with somatotroph macroadenomas provides early significant tumour shrinkage with rapid improvement of visual symptoms at the end of the first month in 50% of patients.